Influence of ADORA2A gene polymorphism on leukoencephalopathy risk in MTX‐treated pediatric patients affected by hematological malignancies. Issue 11 (11th July 2016) - Tsujimoto, Shin‐ichi; Yanagimachi, Masakatsu; Tanoshima, Reo; Urayama, Kevin Y.; Tanaka, Fumiko; Aida, Noriko; Goto, Hiroaki; Ito, Shuichi
Abstract: Background: Methotrexate (MTX) can lead to neurotoxicity and asymptomatic leukoencephalopathy. However, the mechanism of MTX‐related leukoencephalopathy is obscure. MTX and its metabolites inhibit 5‐aminoimidazole‐4‐carboxamide ribonucleotide formiltransferase (ATIC) and promote adenosine release. Recently, it has been reported that adenosine and its receptor are related to certain central nervous system diseases. We investigated whether adenosine pathway gene polymorphisms and clinical factors were related to MTX‐related leukoencephalopathy in pediatric patients affected by hematological malignancies. Procedure: Fifty‐six Japanese childhood acute lymphoblastic leukemia or lymphoma patients were investigated. Patients were evaluated by magnetic resonance imaging of the brain before maintenance therapy or stem cell transplantation. Gene polymorphisms within the adenosine pathway ( ATIC, adenosine A2A receptor [ ADORA2A ]) and the MTX pathway (methylenetetrahydrofolate reductase [ MTHFR ] and ABCB1 ) were genotyped using TaqMan assays. Clinical data were collected by accessing the medical records. MTX‐related leukoencephalopathy was evaluated by a pediatric neurologist. Results: Twenty‐one (37%) of 56 patients developed MTX‐related leukoencephalopathy. Four of 21 patients developed clinical neurotoxicity. The minor allele CC genotype of rs2298383 ( ADORA2A ) was associated with MTX‐related leukoencephalopathy ( P = 0.010, odds ratio = 5.81, 95% confidence interval 1.50–22.50). High cumulative dose of systemic MTX was associated with MTX‐related leukoencephalopathy after adjusting for sex, ADORA2A polymorphism, and prolonged high MTX concentration ( P = 0.042, odds ratio = 1.18, 95% confidence interval 1.01–1.37). Conclusions: ADORA2A rs2298383 and high cumulative dose of systemic MTX administration were significantly associated with MTX‐related leukoencephalopathy. Our results indicate that pharmacological intervention within the adenosine pathway may be both a treatment and preventative option for MTX‐related leukoencephalopathy.